Proximal Femur Fractures An Evidence-Based Approach to Evaluation and Management (Springer International Publishing, 2018)
This timely resource organizes and presents the most up-to-date, evidence-based information on the evaluation and management of all aspects of proximal femur fractures, divided into three succinct sections. Part I discusses basic principles, including anatomy, biomechanics and surgical approaches to the proximal femur. Detailed chapters focusing on individual fracture locations and types comprise part II, such as femoral head and neck fractures, intertrochanteric and subtrochanteric fractures, and nonunions. Optimal perioperative medical management and quality and safety concerns are presented in part III. Each chapter includes a section on evidence-based considerations, and authors present their preferred methods of treatment as well as case examples, where applicable. Providing a quick review of the newest evidence, but also allowing for an in-depth review of the details associated with specific fracture types around the hip, Proximal Femur Fractures provides the orthopedic and trauma surgeon with essential information when preparing for any particular proximal femur fracture procedure.